Quality control in PET/CT and PET/MRI: Results of a survey amongst European countries. (July 2022) - Reynés-Llompart, Gabriel; Zorz, Alessandra; Boellaard, Ronald; Ptáček, Jaroslav; Pike, Lucy; Soret, Marine; Vandenberghe, Stefaan; Matheoud, Roberta
Highlights: EFOMP set a Working Group (WG) to prepare a guideline for PET/CT/MRI Quality Control (QC). The WG set a survey to map the current QCs situation. 123 answers from Medical Physics Experts of 24 countries were collected in the survey. The results show a lack of harmonization in the PET QC procedures across Europe. The collected data will help to tailor a set of simple and practical QCs. Abstract: Purpose: An EFOMP Working Group (WG) was created in 2020 to establish recommendations for PET/CT/MRI Quality Control (QC). The WG's intention was to create a document containing a set of measurements suitable for routine practice. In order to map the current situation in PET facilities, the WG prepared a survey addressed to European Medical Physics Experts (MPE). Methods: The survey was conducted using an electronic questionnaire with 10 sections, for a total of 43 multiple choice or open questions. Data regarding general information, model of installed scanners, contract of maintenance and phantoms available were collected. The focal part of the questionnaire concerned the QC protocol adopted and accreditation programs. Results: 123 answers from 24 countries were collected. 90.2% of the respondents are affiliated as staff MPEs; 45% have non-digital TOF PET/CT scanners with a contract of maintenance (97.6%). In 98.4% and 86.8% of responding centres a sealed source for daily QC and the NEMA Image Quality Phantom were present. 94.3% of respondents perform daily QC according to manufacturer recommendations, while NEMA Tests are not performed routinely (51.2%). 56.1% of the respondents have scanners accredited by a national or international organization. 56% of the centres perform annual CT tests, while more than 90% do not perform any MRI QCs. Conclusions: The results of the survey show that there is a lack of harmonization in the PET QC procedures across Europe. The information obtained will guide the WG in proposing a guideline containing a set of measurements suitable for the clinical routine.